(untitled) (Perner’s Contacts, 2010)
The paper discusses the issue of rewarding for drivers of road freight. The first part of the paper describes the problems of a shortage of drivers. Another part of the paper describes the process of personnel planning in relation to the recruitment of new drivers and keeping of existing drivers. The remaining part describes the contribution of form of salary in road transport business.